Speciation and reactivity of lead and zinc in heavily and poorly contaminated soils: Stable isotope dilution, chemical extraction and model views. (June 2017) - Ren, Zong-ling; Sivry, Yann; Tharaud, Mickaël; Cordier, Laure; Li, Yongtao; Dai, Jun; Benedetti, Marc F.
Abstract: Correct characterization of metal speciation and reactivity is a prerequisite for the risk assessment and remedial activity management of contaminated soil. To better understand the intrinsic reactivity of Pb and Zn, nine heavily and poorly contaminated soils were investigated using the combined approaches of chemical extractions, multi-element stable isotopic dilution (ID) method, and multi-surface modelling. The ID results show that 0.1–38% of total Pb and 3–45% of total Zn in the studied soils are isotopically exchangeable after a 3-day equilibration. The intercomparison between experimental and modelling results evidences that single extraction with 0.43 M HNO3 solubilizes part of non-isotopically exchangeable fraction of Pb and Zn in the studied soils, and cannot be used as a surrogate for ID to assess labile Pb and Zn pools in soil. Both selective sequential extraction (SSE) and modelling reveal that Mn oxides are the predominant sorption surface for Pb in the studied soils; while Zn is predicted to be mainly associated with soil organic matter in the soil with low pH and Fe/Mn oxides in the soils with high pH. Multi-surface modelling can provide a reasonable prediction of Pb and Zn adsorption onto different soil constituents for the most of the studied soils. The modelling could be a promising tool to decipher the underlying mechanism that controls metal reactivity in soil, but the submodel for Mn oxides should be incorporated and the model parameters, especially for the 2-pK diffuse layer model for Mn oxides, should be updated in the further studies. Graphical abstract: Highlights: 0.1–38% of total Pb and 3–45% of total Zn are isotopically exchangeable in the studied soils. Selective sequential extraction could not assess the 'real' metal speciation. Mn oxides are the major sorption surface for Pb in the studied soils and should be incorporated into multi-surface model. The parameters in the 2-pK diffuse layer model for metal binding to Mn oxides should be updated. Abstract : Pb and Zn have different affinities during sorption to soil constituents, multi-surface modelling is a useful tool to decipher the intrinsic metal reactivity and speciation in soil.